Is formal scoring better than just looking? A comparison of subjective and objective scoring methods of the Rey Complex Figure Test for lateralizing temporal lobe epilepsy. Issue 7 (3rd October 2022) - LeMonda, Brittany C.; MacAllister, William; Morrison, Chris; Vaurio, Linnea; Blackmon, Karen; Maiman, Moshe; Liu, Anli; Liberta, Taylor; Bar, William B.
Abstract: Objective Neuropsychologists labor over scoring the Rey Complex Figure Test (RCFT), a measure of visuospatial functioning and nonverbal memory. Compelling arguments suggest that pathognomonic signs of the RCFT are observable to the "naked eye." Standard scoring systems are insensitive to lateralizing temporal lobe epilepsy (TLE) and alternative "qualitative" scoring systems are ineffective and time-consuming. Method: We examined accuracy of TLE lateralization using subjective classifications and standard scoring. Participants were 84 TLE patients (53 female; mean age= 36yrs) and 46 controls (27 female; mean age = 27.5). The former were classified as right (n = 41) or left (n = 43) TLE by neurologists using EEG and MRI studies. RCFT were scored using standard scoring with cut-offs of z ≤ –2 classified as impaired and were rated as "characteristic" of RTLE (Ugly) or LTLE (Not Ugly) performance by neuropsychologists. Accuracy of seizure lateralization for both methods was examined. Results: Neuropsychologists' ratings accuracy were at or below chance. Standard scoring criteria showed chance or slightly better lateralization prediction. Standard scoring predicted RTLE laterality more accurately than subjective ratings for copy trials; standard scoring was no better at lateralizing RTLE with delays. Subjective ratings were better at distinguishing TLE patients from controls. Conclusion: Findings highlight concerns regarding the usefulness of the RCFT in TLE lateralization, regardless of scoring approach.